ANALISIS PENERAPAN TEKNIK SINEMATOGRAFI PADA VIDEO PERSEMBAHAN WISUDAWAN DI LINGKUNGAN PERGURUAN TINGGI - I Gede Nyoman Wisnu Satyadharma; Mario Rinaldi; Annisa Bela Pertiwi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
This research focused on "Analysis of the Application of Cinematographic Techniques in Graduation Presentation Videos in the Higher Education Environment." A qualitative approach using a descriptive method was employed to collect data through video observation and interviews with the production team. Data analysis centered on the concept of John V. Mascelli's "Five C's of Cinematography", which highlights the Five C's of Cinematography. Mascelli's "Five C's of Cinematography" concept, which highlights the Aspects of Composition, Continuity, Cropping, Close Shooting, and Camera Angle. The results showed a good application of the elements of cinematography in the video, featuring a variety of camera angles, good visual continuity, dynamic cutting techniques, the use of close shots to express emotion, and a strong variety of visual compositions. However, the research also revealed potential areas for improvement, especially as technology evolves. Despite the success of the video, the research recommendations suggest further analysis of older similar works as well as investigation into the influence of current technology in video shooting and editing. The conclusions of the research emphasize the successful application of cinematographic techniques in the video, while suggestions for future research call for maximizing the potential for development through the continued use of available technological developments.